Pengaruh Konsep Health Tourism Terhadap Motivasi Kunjungan Wisata ke Sari Ater - Diny Nurul Fitriany; Titing Kartika (Manajemen dan Pariwisata, 2022)
This study aims to determine: (i) the concept of health tourism in Sari Ater; (ii) motivation for tourist visits to Sari Ater; (iii) the influence of the concept of health tourism on the motivation for tourist visits to Sari Ater. The method used in this research is quantitative by distributing questionnaires to a sample of 100 Sari Ater tourists randomly. The results of the questionnaire were processed using the SPSS 24 application by testing the validity, reliability, normality, simple linear regression, t test, and the coefficient of determination. The hypothesis of this study is "There is an influence from the concept of health tourism on the motivation for tourist visits to Sari Ater". The results are: (i) the concept of health tourism in Sari Ater shows an average score of 3.63 in the good category. (ii) the motivation for a tourist visit to Sari Ater shows an average score of 3.63 in the good category. (iii) the effect of the concept of health tourism on the motivation for tourist visits to Sari Ater shows the t value of 11.468 is greater than t table 1.66055 which can be said to have a positive and significant effect. With a RSquare value of 0.573 or 57.3% of the contribution made by the concept of health tourism to the motivation of tourist visits with a pretty good category. At the end of the research, the authors suggest that the main and supporting facilities can be repaired or equipped by Sari Ater.